2020
DOI: 10.3390/diagnostics10060368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scanning Resolution on the Prediction of Trabecular Bone Microarchitectures Using Dental Cone Beam Computed Tomography

Abstract: Assessing bone quality and quantity at the location of dental implants before dental implantation is crucial. In recent years, dental cone-beam computed tomography (dental CBCT) has often been used to assess bone quality and quantity prior to dental implant. However, the effect of scanning resolution on the prediction of trabecular bone microarchitectural parameters (TBMPs) remains unclear. The objective of this study was to examine how dental CBCT with various scanning resolution differs with regard to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…In our study, we found no statistically significant differences in FD values between CBCT images taken with different FOV sizes. This finding is consistent with a study by Tsai et al ( 25 ), which evaluated the effects of scanning protocols on bone microarchitecture in CBCT images using the ImageJ program and found that resolution mode did not affect the trabecular parameters. However, it should be noted that there are studies in the literature indicating that changes in CBCT scanning parameters can alter image quality ( 27 , 28 , 29 , 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found no statistically significant differences in FD values between CBCT images taken with different FOV sizes. This finding is consistent with a study by Tsai et al ( 25 ), which evaluated the effects of scanning protocols on bone microarchitecture in CBCT images using the ImageJ program and found that resolution mode did not affect the trabecular parameters. However, it should be noted that there are studies in the literature indicating that changes in CBCT scanning parameters can alter image quality ( 27 , 28 , 29 , 30 ).…”
Section: Discussionsupporting
confidence: 92%